Functionalized gold nanoflowers on carbon screen-printed electrodes: an electrochemical platform for biosensing hemagglutinin protein of influenza A H1N1 virus - Carlos Enrique Torres-Méndez; Sharmilee Nandi; Klara Martinovic; Patrizia Kühne; Yifan Liu; Sam Taylor; Maria Lysandrou; Maria Ines Berrojo Romeyro Mascarenhas; Viktoria Langwallner; Javier Enrique Sebastián Alonso; Ivana Jovanovic; Maike Lüftner; et al. (Beilstein Journal of Nanotechnology)
An electrochemical biosensor based on modified carbon screen-printed electrodes was developed for the detection of hemagglutinin of influenza A H1N1 virus (H1). Gold nanoflowers were electrodeposited on the electrode to increase conductivity and surface area. The electrochemical signal was amplified by functionalization of the gold nanoflowers with 4-aminothiophenol, which resulted in a 100-fold decrease of the charge transfer resistance due to a tunneling effect. Subsequently, monoclonal antibodies against H1 were immobilized on the surface via covalent amide bond formation, followed by blocking with bovine serum albumin to minimize nonspecific hydrophobic binding. The electrodes were characterized by cyclic voltammetry and electrochemical impedance spectroscopy experiments in the presence of [Fe(CN)6]3−/4−. Differential pulse voltammetry was used to measure the change in current across the electrode as a function of H1 concentration. This was performed on a series of samples of artificial saliva containing H1 protein in a clinically relevant concentration range. In these experiments, the biosensor showed a limit of detection of 19 pg/mL. Finally, the biosensor platform was coupled to an automated microfluidics system, and no significant decrease of the electrochemical signal was observed.